2011
DOI: 10.1159/000327351
|View full text |Cite
|
Sign up to set email alerts
|

Intake of Medication and Vitamin Status in the Elderly

Abstract: Background/Aims: An inadequate vitamin status is associated with higher morbidity and frailty in the elderly and might be due to medication. This study aimed to evaluate the status of several vitamins in relation to regular intake of medication in this population. Methods: A total of102 non-institutionalized subjects aged 70–90 years were recruited. Plasma levels of vitamins A, D, E, K and C were determined by HPLC. The functional parameters of vitamins B1, B2 and B6, i.e. the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…The long‐term intake of a judiciously composed nutriceutical containing low‐dose vitamins, antioxidants, minerals and particular herbal preparations seems justified for older persons who take medication (Fabian et al ., ), or who consume an unbalanced diet (Ulbricht, ), or who are exposed to environmental toxins. It may be advisable to combine this nutriceutical with hormone replacement therapy, whenever the latter is needed.…”
Section: Resultsmentioning
confidence: 99%
“…The long‐term intake of a judiciously composed nutriceutical containing low‐dose vitamins, antioxidants, minerals and particular herbal preparations seems justified for older persons who take medication (Fabian et al ., ), or who consume an unbalanced diet (Ulbricht, ), or who are exposed to environmental toxins. It may be advisable to combine this nutriceutical with hormone replacement therapy, whenever the latter is needed.…”
Section: Resultsmentioning
confidence: 99%
“…The recent literature regarding medication intake focuses primarily on elderly (>65 years), institutionalized or hospitalized patients [ 12 , 13 , 14 , 15 , 16 ], and only a few publications included measures of micronutrients [ 12 , 14 ]. Bates et al showed that 78% of British elderly (>65 years) living in the community and 93% of those in institutions were using medication.…”
Section: Discussionmentioning
confidence: 99%
“…However, the impact of medication intake on plasma micronutrient concentrations has been scarcely studied and previous studies focused mainly on the association between polypharmacy and general nutritional status—but not single micronutrients—in older individuals (>65 years), in institutionalized persons or in hospitalized patients [ 12 , 13 , 14 , 15 ]. To the best of our knowledge, most data on the general frequency of medication intake originate only from older populations [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The combination of substances with complementary effects is expected to act in synergisms. The NFS generally aims at complementing dietary deficiencies, particularly in elderly persons [4] and patients taking medication [5]. In the metabolic syndrome, a specific NFS focusses on reducing the impact of inflammation and of oxidative overload, and on correcting the impaired metabolism.…”
Section: Introductionmentioning
confidence: 99%